Intraoperative Ramsay Sedation Score after Dexmedetomidine Infusion in Patients Undergoing Perineal Surgeries - Samrah Shafqat, Sadaf Zehra, Shahneela Raza, Alina Siddiqui, Samia Mobin, Nadeem Muneer (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the intraoperative Ramsay sedation score after dexmedetomidine infusion in patients undergoing perineal surgery. Study design: Descriptive study. Place and duration of study: Department of Anaesthesia, JPMC, Karachi from 13th February 2021 to 13th August 2021. Methodology: One hundred and seventy four patients who met the diagnostic criteria were enrolled. Results: The mean age was 46.51 years with the standard deviation of ±10.87. 66 (37.9%) were male and 108 (62.1%) were female. Whereas, mean duration of surgery, Ramsay sedation score at 5 minutes, 15 minutes, 30 minutes, height, weight and BMI in our study was 1.41±0.40 hours, 1.72±0.44, 3.51±0.60, 4.57±0.62, 165.62±8.23 cm, 68.34±8.23 kg and 24.85±3.34 kg/m2 respectively. Conclusion: Intraoperative dexmedetomidine proved beneficial in perineal surgeries and could be served as a potent sedative drug. Keywords: Ramsay sedation score, Anesthesia, Dexmedetomidine, Pain, Perineal surgery, Sedation